Astaxanthin determination in marine biological samples : an overview - Darias-Hernández, Tania (2013)
Máster en Oceanografía Astaxanthin (AX) is a pigment that belongs to the family of the xanthophylls, the oxygenated derivatives of carotenoids whose synthesis in plants derives from lycopene. AX, which may not be synthesized de novo by animals, is one of the main pigments in marine ecosystems found in crustacean, and many fish species. In pelagic marine food webs, copepods are the main producers of AX, being also the principal components of Antarctic Krill pigment. Thus, in the aquaculture industry AX is present in feed formulations for salmonids and other farmed fish species, where represent an important cost of the feeds.